Liquid-Liquid-Liquid Three Phase Extraction Apparatus： Operation Strategy and Influences on Mass Transfer Efficiency - 何秀琼 黄昆 于品华 张超 谢铿 李鹏飞 王娟 安震涛 刘会洲 (Chinese journal of chemical engineering, 2012)
Abstract A new mixer-settler-mixer three chamber integrated extractor is proposed in this work for liquid-liquid- liquid three phase countercurrent and continuous extraction. Experiments revealed the influences of the structural design of the three-liquid-phase extractor and some key operational parameters on three-phase partition of two phenolic isomers, p-nitrophenol （p-NP） and o-nitrophenol （o-NP）. The model three-liquid-phase extraction system used here is nonane （organic top-plaase）-polyethylene glycol （PEG 20UU） （polymer mlddle-phase）-（NH4）2SO4 aqueous solution （aqueous bottom-phase）. It is indicated that agitating speed and retention time in three-phase mixer are key parameters to extraction fraction of nitrophenol. Dispersion band behavior is related to agitating intensity, and its occurrence does not affect the extraction fraction of target compounds. The present work highlights the possibility of a feasible approach of scaling up of the proposed three-phase extraction apparatus for future in- dustrial-aimed applications.